Synthesis and preliminary stability study of natrosol gels containing Hamamelis virginiana extract (Research, Society and Development, 2023)
Hamamelis extract is an excellent anti-inflammatory due to its vasodilator action, used by the pharmaceutical industry in the form of an anti-varicose gel. The aim of this study is to evaluate the thermal stability of five Natrosol® gel formulations containing witch hazel extract. During the preliminary stability test, the gels were subjected to 6 cycles of thermal stress, using temperatures of 45±2°C and 5±2°C, respectively, for 24 each, equivalent to 1 cycle. At the end of each freeze-thaw cycle, each formulation was analyzed through organoleptic characterization (color, odor and appearance), pH and density, and statistical analysis of the data obtained was applied. Formulation 2, presented at certain times, turbidity in its color, indicating unfeasibility of the sample, differing however, from the rest of the formulations, which presented a positive character, preserving its stability throughout the analyses, performing in compliance with the stability guides. Thus, F1, F3, F4 and F5 demonstrate the viability of moving on to the next long-term stability steps.